Age‐related alterations in functional connectivity along the longitudinal axis of the hippocampus and its subfields. Issue 1 (12th September 2020) - Stark, Shauna M.; Frithsen, Amy; Stark, Craig E.L.
Abstract: Hippocampal circuit alterations that differentially affect hippocampal subfields are associated with age‐related memory decline. Additionally, functional organization along the longitudinal axis of the hippocampus has revealed distinctions between anterior and posterior (A‐P) connectivity. Here, we examined the functional connectivity (FC) differences between young and older adults at high‐resolution within the medial temporal lobe network (entorhinal, perirhinal, and parahippocampal cortices), allowing us to explore how hippocampal subfield connectivity across the longitudinal axis of the hippocampus changes with age. Overall, we found reliably greater connectivity for younger adults than older adults between the hippocampus and parahippocampal cortex (PHC) and perirhinal cortex (PRC). This drop in functional connectivity was more pronounced in the anterior regions of the hippocampus than the posterior ones, consistent for each of the hippocampal subfields. Further, intra‐hippocampal connectivity also reflected an age‐related decrease in functional connectivity within the anterior hippocampus in older adults that was offset by an increase in posterior hippocampal functional connectivity. Interestingly, the anterior–posterior dysfunction in older adults between hippocampus and PHC was predictive of lure discrimination performance on the Mnemonic similarity task (MST), suggesting a role in memory performance. While age‐related dysfunction within the hippocampal subfields has been well‐documented, these results suggest that the age‐related dysfunction in hippocampal connectivity across the longitudinal axis may also contribute significantly to memory decline in older adults.